Rancang Bangun Software Universal Astrolabe Berbasis Javascript dan Uji Akurasinya dalam Hisab Arah Kiblat - Nahwandi, M. Syaoqi; Setyawan, Edy; Nadirin, Akhmad (Mahkamah : Jurnal Kajian Hukum Islam, 2024)
The astrolabe, as a classical astronomical instrument, holds significant historical and educational value, yet its use has become limited due to technological advancements. This study aims to develop a JavaScript-based Universal Astrolabe software to digitize the functions of a physical astrolabe, with a focus on testing the accuracy of Qibla direction calculations. The Research and Development (R&D) method was implemented through stages of needs analysis, design, implementation, and accuracy testing. Test results from three locations (Cirebon, Kuala Lumpur, Istanbul) showed minor discrepancies (0°1'56"–0°4'20") between the software's calculations and those derived from the spherical triangle formula using a calculator. These differences were attributed to the smallest rotation angle rounding of the Rete (0°15') and the 1° interval scale for altitude and azimuth. The software offers advantages in flexibility, automated Rete positioning, and ease of presentation compared to physical astrolabes, though it does not replace the function of direct observation. The interactive simulation of the Universal Astrolabe software facilitates its use for educational purposes in Islamic astronomy (Ilmu Falak).